2022
DOI: 10.5539/jfr.v11n1p28
|View full text |Cite
|
Sign up to set email alerts
|

Technological and Nutritional Aspects of Incorporating Jamun (Syzygium cumini (L.) Skeels) Fruit Extract into Yoghurt

Abstract: The study aimed to evaluate the technological suitability of incorporating the jamun extracts into Yoghurt. The light focused on the effect of the extraction method and rate of addition on the flavonols profiles, antioxidant activity and sensorial characteristics of the final Yoghurt product. Jamun fruit was subjected to either mechanical cold extraction or steam extraction and introduced to milk at rates of 5 and 10%. The results indicated that the extraction technique had no effect on the values of protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A study was conducted to evaluate the possibility of developing jamun juice in yogurt preparation. The results showed that 5% jamun juice-incorporated yogurt presented greater overall acceptability with higher flavonols levels and anti-oxidant potential (Emam and El-Nashar, 2022). A study was conducted by Suradkar et al (2021) to identify the storage stability of jamun fruit bar using different packaging material.…”
Section: Value-added Products From Jamunmentioning
confidence: 99%
“…A study was conducted to evaluate the possibility of developing jamun juice in yogurt preparation. The results showed that 5% jamun juice-incorporated yogurt presented greater overall acceptability with higher flavonols levels and anti-oxidant potential (Emam and El-Nashar, 2022). A study was conducted by Suradkar et al (2021) to identify the storage stability of jamun fruit bar using different packaging material.…”
Section: Value-added Products From Jamunmentioning
confidence: 99%
“…A new export market might be opened up by turning jamun fruits into a variety of exotically favored products with higher nutritional and sensory properties. Jamun pulp, dried jamun, fermented jamun products, or seed powder have all been used to create a variety of products [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%